2005
DOI: 10.1111/j.1540-8159.2005.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial Atrial Standstill in Association with Dilated Cardiomyopathy

Abstract: . Atrial standstill is an extremely uncommon arrhythmia that rarely appears to be familial and genetically determined. Atrial standstill has been associated with several conditions including, but not restricted to, congenital heart disease, valvular heart disease, conduction disturbances, Brugada syndrome, myocardial infarction, and amyloidosis. Only a few cases of familial clustering of atrial standstill have been reported so far. This report represents a family with atrial standstill associated with syncope,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Isolated atrial standstill was reported for the first time by Harley (5). Atrial standstill in association with dilated cardiomyopathy and ventricular tachycardia has been reported too (6). The cause of abnormality in this patient is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated atrial standstill was reported for the first time by Harley (5). Atrial standstill in association with dilated cardiomyopathy and ventricular tachycardia has been reported too (6). The cause of abnormality in this patient is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Symptomatic cases require ventricular pacing and treatment for congestive heart failure if present, however, the prognosis is poor. Fazelifar et al1 reported a family with atrial standstill associated with syncope, dilated cardiomyopathy, and sudden cardiac death, and agreed with the postulation that the atrial standstill is a disease primarily associated with SCN5A mutation and rare connexin 40 genotype 5. Bhuiyan et al9 presented two families with typical CPVT in conjunction with additional features of progressive AV block, sinus node dysfunction, atrial fibrillation, atrial standstill, and dilated cardiomyopathy those related with the genetic defect in the N-terminus of RYR2.…”
Section: Discussionmentioning
confidence: 99%
“…On surface ECG, atrial standstill is distinguished by bradycardia, junctional (usually narrow complex) or wide complex escape rhythm, and absence of the P wave 1. Atrial standstill can be persistent or transient, and diffuse or partial.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] There also may be an association with cardiomyopathy. [11][12][13] To our knowledge, the current case is the first detailed electrophysiological assessment of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…However, an association with syncope and sudden death indicates that the syndrome may not always be benign. 1,11,30 This could result from inconsistencies in the junctional escape rhythm responsible …”
Section: Varma Et Al Sinus Node Dysfunction and Atrial Standstill E55mentioning
confidence: 99%